Physico-chemical Properties of Various Types of Wastewaters Used as Source of Irrigation - Javed, Amna; Shehzadi, Samreen; Ahmad, Tanveer; Shah, Syed Azam (The Nucleus, 2023)
Wastewater is widely used for irrigation of agricultural lands due to scarcity of freshwater, its reliable supply and high nutrients value. However, untreated wastewater is mostly contaminated with organic pollutants and toxic heavy metals including: cadmium (Cd), chromium (Cr), mercury (Hg), lead (Pb), copper (Cu), nickel (Ni), zinc(Zn), cobalt (Co), Iron (Fe), molybdenum (Mo) and boron (B). Therefore, chemical analyses of wastewater is of great concern for safe agricultural irrigation. A study was conducted at Central Analytical Facility Division (CAFD) of Pakistan Institute of Nuclear Science and Technology (PINSTECH), Islamabad with the objective to collect various types of wastewater and analyze for their nutrient composition (macro & micronutrients), heavy metals content (As, Hg, Cr, Cd, Pb, Ni) and other physicochemical characteristics including: pH, electrical conductivity (EC), total dissolved solids(TDS), total suspended solids(TSS), chemical oxygen demand (COD) and biological oxygen demand (BOD). Three categories of wastewater including sewage water, industrial wastewater and domestic wastewater being used as irrigation source were collected from various places and were analyzed using atomic absorption spectrometry (AAS) and inductively coupled plasma- optical emission spectrometry (ICP-OES). The obtained results revealed that domestic wastewater (Shah Town, Islamabad) and industrial wastewater (Hayatabad, Peshawar) were found environmentally safe. It was found that sewage water collected from Tarlai farms, Islamabad had no toxic heavy metals except mercury (2.67 ng mL-1) which was slightly above than FAO safe limits. However, sewage water collected from Sohan village, Islamabad is not recommended for irrigation due to its high mercury content (342.14 ng mL-1).